Nilai-Nilai Pendidikan Karakter dalam Al-Qur’an dan Relevansinya dengan Filosofi Jou Se Ngon Sabua Masyarakat Ternate - Salehuddin Mattawang; Achmad Dardirie; Irfan; Muhammad Amri; A'raf Saefuddin (Institut Agama Islam Negeri Pontianak, 2026)
This study examines the values of character education contained in the Qur’an through a thematic (maudhu’i) approach and their relevance to the philosophy of Jou Se Ngon Sabua as the local wisdom of the Ternate community, North Maluku. The moral crisis affecting the younger generation today requires solutions that are rooted not only in normative religious texts but also in local cultural values that have long been embedded in community life. Using a library research method based on thematic exegesis and an ethnopedagogical approach, this study identifies seven fundamental character values in the Qur’an: tawhid (divine unity), honesty (shidq), justice (‘adl), compassion (rahmah), responsibility, brotherhood (ukhuwwah), and humility (tawadhu’). These values have a profound relevance to the dimensions of the Jou Se Ngon Sabua philosophy, both in its vertical dimension (the relationship between humans and God) and its horizontal dimension (the relationship between human beings). This study concludes that the philosophy of Jou Se Ngon Sabua can serve as a cultural bridge in the internalization of Qur’anic values in Islamic education in Ternate.